A virophage at the origin of large DNA transposons - Fischer, Matthias G; Suttle, Curtis A (Science (American Association for the Advancement of Science), 2011)
DNA transposons are mobile genetic elements that have shaped the genomes of eukaryotes for millions of years, yet their origins remain obscure. We discovered a virophage that, on the basis of genetic homology, likely represents an evolutionary link between double-stranded DNA viruses and Maverick/Polinton eukaryotic DNA transposons. The Mavirus virophage parasitizes the giant Cafeteria roenbergensis virus and encodes 20 predicted proteins, including a retroviral integrase and a protein-primed DNA polymerase B. On the basis of our data, we conclude that Maverick/Polinton transposons may have originated from ancient relatives of Mavirus, and thereby influenced the evolution of eukaryotic genomes, although we cannot rule out alternative evolutionary scenarios.